Effect of Tax Planning on Corporate Value with Audit Quality Moderating - Nanik Lestari; Windya Roshinta (Politeknik Negeri Batam, 2022)
This study is aimed to provide empirical evidence for companies and investors in the form of information that is important to determine the effect of tax planning level on corporate value with audit quality as moderating variable. This study used quantitative approach method, data retrieval technique using purposive sampling method. In addition, the sample of this study amounts to 365 all sectors companies listed on the Indonesia Stock Exchange (BEI), except financing and mining sectors. Data analysis technique used is panel data regression analysis. The results showed that the level of tax planning has a negative significant influence on value of the company. Audit quality has no significant influence on value of the company and could give a weakness effect on relationship of tax planning influence on value of company. Moreover, the variable in this study which are SIZE, LEV, & TANG as control variables significantly influence the value of the company. FAG as control variable has no significant influence on the value of company. This states that increased tax planning will decrease the value of the company. In fact, audit quality factor could not be influencing the company value yet. This study is limited to all sectors companies listed on Indonesia Stock Exchange period 2012-2015 except financing and mining. In conclusion, the further of this study are suggested to use other variables related to research and samples from other industries with longer period of year.